A CRITICAL REVIEW ON THE APPLICATION OF YUKTI PRAMANA FOR THE LOGICAL INCLUSION OR REJECTION OF A DRUG MENTIONED IN OUSHADHA YOGA (MEDICINAL FORMULATIONS) ACCORDING TO CLINICAL CONDITION - T P, *Sinimol; P.P, Meghna; M.C, Soumya (International Journal of Ayurveda and Pharma Research, 2018)
An Ayurvedic physician usually depends on classical compound medicinal formulations for treating patients. Sometimes, patients themselves demand us that they will prepare the medicines themselves, especially Kwatha (decoctions). One reason is the superior efficacy of the self prepared medicines than the bottled decoctions due to the presence of chemical preservatives. While preparing formulations, we may need to add or delete drug/drugs depending on the clinical condition of the patient. Scarcity of herbal drugs is also another reason which compels us for substitution. In Bhavaprakasha, there is a reference stating that any drug which is inappropriate and unsuitable to a disease, even though found included in the drug group or medicinal formulae may be rejected and any drug which is found suitable or appropriate may be included though not mentioned in it. There are so many references in Ayurvedic classics where we can see deletion or inclusion of drugs in a formulation according to the condition of the patient or disease. This is an attempt to analyse the logic (the application of Yukti pramana) behind it. This article also want to depict the relevance of logically changing the contents of a medicinal formulation by analyzing its Rasapanchaka (five Ayurvedic principles of drug action), depending on the condition of disease or patient.